Mathematical critical thinking and resiliency: Experiment of grade-7 students using scientific approah - Rohaeti, Euis Eti; Koswara, Dadang (Jurnal Riset Pendidikan Matematika, 2018)
The purpose of this study was to describe the role of scientific approach on students’ mathematical critical thinking and resiliency. This study wass a pre test-post test experimental control group design and involves 66 seventh grade students as sample. Data collection was conducted by a mathematical critical thinking test, a mathematical resiliency questionnaire, and a perception on scientific approach questionnaire. Data analysis was conducted using descriptive and inferential analysis. The study found that on mathematical critical thinking ability, students getting treatment by scientific approach attained better than students taught by conventional teaching, but both groups were still at low level. On mathematical resiliency, there was no different between students on both teaching approaches, and those groups were at medium level. The other findings, there was no association between mathematical critical thinking ability and mathematical resiliency, and students performed high perception toward scientific approach.